Increased uric acid to high-density lipoprotein ratio positively correlated with stroke risk - Zhu, Tieshi; He, Yong; Bei, Erxinxian (Frontiers in Neurology, 2025)
BackgroundThe Uric Acid-to-HDL Ratio (UHR), a novel index derived from serum uric acid and high-density lipoprotein, has been linked to hypertension and poor diabetes control. It has also been shown to predict ischemic heart disease and is strongly associated with collateral circulation and coronary artery flow reserve. However, fewer studies have focused on the relationship between UHR and stroke, highlighting the need for further research in this area.MethodsThe study included 33,192 individuals from the NHANES 1999–2023, of whom 1,363 had a history of stroke. The nonlinear relationship between UHR and stroke risk was assessed using restricted cubic spline (RCS) analysis, and the robustness of the findings was further tested through stratified analysis. Logistic regression was employed to analyze the relationship between UHR and stroke risk, considering both UHR as a continuous variable and its categorization into quartiles (Q1–Q4).ResultsUHR was not nonlinearly associated with stroke (p for overall <0.01; p for nonlinearity = 0.65), and the RCS graph approximated a straight line with a positive slope. UHR was significantly associated with an increased risk of stroke, both when analyzed as a continuous variable (Model 4: OR = 1.02, 95% CI 1.01–1.03, p < 0.01) and when categorized into quartiles (Q4, OR = 1.31, 95% CI 1.11–1.55, p < 0.01).ConclusionThere was a significant positive correlation between UHR and stroke risk.